Wanna try something crazy? - Tee, Charmaine (Nanyang Technological University, 2023)
This film aims to combine elements of 2D and 3D to create a stylistic animation. Following the story of a man who harmlessly takes his date home for a wild night, unbeknownst to the horrors of what eventually happens. This film was animated in 3D on Maya with 2D hand painted backgrounds in Photoshop. By paying more attention to textures and consistency, we were able to achieve a painterly animated film.